(3Gdbhd GdeSJXQa aj SaQ GdSdWGf Gdedc GdCTQa (B( (3CHj GdfUQ bGjJHGi (B)s - (3GHf GdLjYGf , CMeO Hf jMji TGcQ Hf YHO GdZfj, TgGH GdOjf CHh GdHbGA,J (B930 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YeQ eeGdc GdESdGe HSdWGffG GdCTQa , hCdgeg GdSjQ EdjgG hGdfXQ ai CeQgG HYO eG cGf MGdgG Ydi GdaSGO CTQa hHYO aEfg deG Cdge Gdgd GdSdWGf GdeGdc Gdedc GdCTQa CHh GdfUQ bGjJHGi Edi GdeSjQ Edi GdeeGdc GdTGejI s
(3BNQgG (B:s
(3hCfTO dSGf GdMGd hbGd (B: (3HbjJ dHfGA GdOgQ jG cga edcg hgPG OYGA ddHQjI TGed jG ef EPG eG OYhfG HGdHbGA dg cfG dCfaSfG fOYhG hfHJgd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B203s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1708 / 4) s
Keywords: (3GdJGQjNs